Tyranny, complaint and redress: the evidence of the petitions presented to the crown c.1320 to 1335 - Walker, Sharon Irene (2013)
This thesis offers a new approach to the understanding of the recurrent crises of the period c.1320 to 1335, covering the final years of Edward II’s turbulent reign, the deposition, and its repercussions into the period of the Regency and the first years of the majority rule of Edward III. This has been achieved through an archive led study of the accounts of the ‘complaint and redress’ encompassed in the records of the Ancient Petitions presented to the Crown, held by The National Archives and designated as the SC 8 series. These records contain some of the most vivid contemporary and individual records of the lives and concerns of the king’s subjects during this turbulent period. This thesis illustrates that these records contain the genuine ‘voice’ of the petitioners, and can be used to reveal the impact on those seeking the king’s justice during the recurring crises of this defining moment in late medieval English history.